“Russian Garrick” and his French Shakespeare: “Les Tombeaux de Vérone” by L.-S. Mercier in V. Pomerantsev’s interpretation - Elena M. Lutsenko (Литературный факт)
The methodology of the article is based on the ideas of historical poetics by A.N. Veselovsky and M.M. Bakhtin. The author examines the reception of Shakespeare’s heritage in Russia in the last third of the 18th century. This idea is demonstrated in the analyses of the adaptation of the bourgeois drama The Tombs of Verona (L.-S. Mercier) by V.P. Pomerantsev (the first Russian interpreter of the plot of Romeo and Juliet). In this regard, the author focuses on the genre poetics of Mercier’s play and Pomerantsev’s translation in their correlation to the poetological and pragmatic factors of the epoch. Special attention is paid to the sources of the plot of Mercier’s play, thus confirming the idea of the indirect reception of Shakespeare’s heritage in Europe (and Russia) in the 18th century as well as its genre transformation. Despite the similarity of the genre of Mercier’s play and its Russian interpretation, discrepancies are revealed at the level of poetics. Mercier replaces sonnet imagery vital for Shakespeare’s play with the images familiar to his contemporaries, i. e., the elegiac intonations of E. Parny. Russian readers became acquainted with Parny’s poetry long after Pomerantsev’s translation. That’s why the translator replaced Parny’s gallant imagery with the elegiac imagery of the Russian verse of the 18th century (much more ponderous than Parny’s) as well as with the intonations of the Russian Rousseau. Mercier’s play, like most 18th-century adaptations of Romeo and Juliet, ends happily. Pomerantsev agrees with it because he perceives the genre of this plot as a bourgeois drama, not a tragedy.